Problematika Kinerja Pengurus Masjid di Tapanuli Selatan - Armyn Hasibuan; Dame Siregar (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2018)
The background of this research was about the existence of problems for mosque administrators in South Tapanuli Regency, namely idarah, imarah andri'ayah. Hence, the researchers investigated the performance of the mosque administrator, the problems faced, and the solutions to overcome those problems in the management of mosque. The researchers used qualitative research with phenomology approach. The data was collected by interviews and observation. The results showed that the problems of performance of mosque administrators was low knowledge and did not understand the organization the mosque according to the guidelines of Directorate General of Islamic Education. It made the management and operation of the mosque did not optimal and well directed. The solution to overcome those problems done organizational development and administration of empowerment for mosque administrators in order to improve performance in prospering the mosque. Key words: Mosque Administrator, Management of Mosque